Inclusão de alunos autistas no contexto escolar: qualificação profissional do educador - Nascimento, Liandra Stefane Oliveira (Brasil, 2024)
The research stems from questions raised during the development of Supervised Internships in Early Childhood Education and Early Years of Elementary School at a federal public higher education institution (HEI) about the inclusion of students with Autism Spectrum Disorder (ASD) in the school context in a public school in the municipality of Manaus in the mesoregion of Centro Amazonense. The methodology is based on a qualitative-quantitative research approach, as it seeks to understand the challenges and training needs of teachers who have students with ASD in the ordinary classroom, so that inclusion can take place in the school environment in an Amazonian reality. In order for the research to achieve the expected results, an observational analysis was used which, in turn, led us to the environment explored. The teachers who took part in the research were familiar with the subject, but still need specific training courses related to the teaching and learning process of students with ASD. Regardless of this fact, for these students to be included in ordinary education, respect for the limits imposed by the disorder and the use of resources must be fundamental for them to feel part of the society in which they live and agents of rights, such as education, priority care, social assistance, culture, sport, among others.